Dampak Keterbukaan Perdagangan terhadap Ketimpangan Pendapatan di Indonesia - Wiguna, Ayas T.; Panennungi, Maddaremmeng A. (Jurnal Ekonomi dan Pembangunan Indonesia, 2019)
Debates over the effect of trade openness on inequality across regions in a country have been arising. Mainly apply on developing countries, such as Indonesia, trade openness affect different level of development across regions. This study is aimed at determining the effect of trade openness on inequality within provinces in Indonesia. A panel data analysis of 33 Indonesian provinces in the period of 2006–2015 has showed that trade openness has no significant effect on regional inequality.